Functional identification of potential non-canonical N-glycosylation sites within Cav3.2 T-type calcium channels - Ficelova, Vendula; Souza, Ivana A; Cmarko, Leos; Gandini, Maria A; Stringer, Robin N; Zamponi, Gerald W; Weiss, Norbert (Molecular brain, 2020)
Low-voltage-activated T-type calcium channels are important contributors to nervous system function. Post-translational modification of these channels has emerged as an important mechanism to control channel activity. Previous studies have documented the importance of asparagine (N)-linked glycosylation and identified several asparagine residues within the canonical consensus sequence N-X-S/T that is essential for the expression and function of Cav3.2 channels. Here, we explored the functional role of non-canonical N-glycosylation motifs in the conformation N-X-C based on site directed mutagenesis. Using a combination of electrophysiological recordings and surface biotinylation assays, we show that asparagines N345 and N1780 located in the motifs NVC and NPC, respectively, are essential for the expression of the human Cav3.2 channel in the plasma membrane. Therefore, these newly identified asparagine residues within non-canonical motifs add to those previously reported in canonical sites and suggest that N-glycosylation of Cav3.2 may also occur at non-canonical motifs to control expression of the channel in the plasma membrane. It is also the first study to report the functional importance of non-canonical N-glycosylation motifs in an ion channel.
Keywords: Asparagine; asparagin; Structure-Activity Relationship; vápníkové kanály - typ T; lidé; Non-canonical glycosylation; Calcium Channels, T-Type; vztahy mezi strukturou a aktivitou; Asparagine-linked glycosylation; Calcium channel; Humans; Amino Acid Motifs; cav3.2 Channel; aminokyselinové motivy; T-type channel; glykosylace; Glycosylation; Trafficking; N-glycosylation